Effectiveness of nifedipine compared with other antihypertension on hypertension during pregnancy - Juwita Permata Sari; Aisyah Nur Sapriati; Cyndi Yulanda Putri; Satya Prima Kustanto; Umu Kholifah (Indonesian Journal of Pharmacology and Therapy, 2022)
Hypertension is the most common complication of pregnancy. It is a major cause of maternal, fetal, and neonatal morbidity and mortality. In this article, the effectiveness of nifedipine compared with other antihypertensives in pregnant women with hypertension was reviewed. The randomized control trial (RCT) of nifedipine and other antihypertension in pregnancy without complications published from 2016 to 2021 in Google Scholar, Cochrane and PubMed were gathered. It was reported that antihypertensives administration to pregnant women with hypertension was very meaningful both for the mother herself and for the fetus or baby. Furthermore, nifedipine has better effectiveness in lowering blood pressure compared to other antihypertensives such as IV labetalol, oral labetalol, IV hydralazine, methyldopa in the treatment of preeclampsia, severe preeclampsia, severe pre-eclampsia/eclampsia, chronic hypertension, hypertension emergency, and severe hypertension.